The Importance of PKn Learning in Forming the Value of Character Education in Primary School Children - Jefri Habibiy Nasution (International Journal of Students Education, 2024)
This research aims to find out how important the influence of learning is in shaping the value of character education in elementary school children. This research is based on the author’s concern about the situation that continues to decline and deviate from character education in the nation’s next generation, especially elementary school children. The method used is a literature review method , in which the author reads and explores topics from various sources such as journals, books and other sources that he feels are related. The results of this research state that character education is important as a bridge in the formation of character education for the nation’s next generation. Through this, it is hoped that the nation’s next generation will not only develop in terms of knowledge and skills but also have noble character.